1961
DOI: 10.1083/jcb.10.4.475
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Vaccinia Virus in Earle's L Strain Cells as Examined by Electron Microscopy

Abstract: A favorable system which is amenable to frequent and reproducible sampling, consisting of suspension cultures of strain L cells and vaccinia virus, was employed to study the animal virus-mammalian host cell relationship. The three principal aspects investigated concerned the adsorption and penetration of vaccinia into the host, the relationship between the sequence of virus development and the production of infectious particles, and the changes in the fine structure of the host cells. Experiments in which a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
1

Year Published

1963
1963
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(140 citation statements)
references
References 19 publications
8
131
1
Order By: Relevance
“…This antibody (Hu anti-VACV Ab) originated from an individual who had been vaccinated five times against smallpox and contained 52% of anti-IMV and 3% of anti-EEV activity compared with Rb anti-VACV Ab (43). The results demonstrated the benefit of HP in combination with human antibody (versus Hu anti-VACV Ab alone; P Ͻ 0.05 for weight loss and signs of illness, days [4][5][6][7][8][9][10]. This suggested that PAs may be used in conjunction with vaccinia-immune globulin in treating smallpox and vaccinerelated complications.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This antibody (Hu anti-VACV Ab) originated from an individual who had been vaccinated five times against smallpox and contained 52% of anti-IMV and 3% of anti-EEV activity compared with Rb anti-VACV Ab (43). The results demonstrated the benefit of HP in combination with human antibody (versus Hu anti-VACV Ab alone; P Ͻ 0.05 for weight loss and signs of illness, days [4][5][6][7][8][9][10]. This suggested that PAs may be used in conjunction with vaccinia-immune globulin in treating smallpox and vaccinerelated complications.…”
Section: Resultsmentioning
confidence: 93%
“…IMV is surrounded by one lipid membrane (5)(6)(7)(8)(9) and is physically robust to aid virus transmission between hosts. CEV and EEV are IMV particles wrapped with an additional membrane derived from the trans-Golgi network (10) or endosomes (11) and are responsible for virus dissemination within the host (4).…”
mentioning
confidence: 99%
“…It is now certain that information on this could be expected only from close study of infected cells at a stage earlier than any in the present series. The demonstration recently of the phagocytosis and subsequent breakdown of vaccinia virus particles (Dales & Siminovitch, 1961) encourages the speculation that infectious particles of trachoma, and others in the psittacosis group, may be taken into the cell in this way. Certainly, the finding of conspicuous lysosome aggregates 6 hr.…”
Section: Discussionmentioning
confidence: 99%
“…An induced membrane proliferation is also observed with Russian spring-summer encephalitis, St. Louis encephalitis and dengue-2 viruses (Murphy, 1980). In other virus infections such as mengovirus (Amako & Dales, 1967), vaccinia virus (Dales & Siminovitch, 1961) and poliovirus (Caliguiri & Tamm, 1970), initiation of RNA synthesis is associated with smooth membranes.…”
Section: Short Communicationmentioning
confidence: 79%